Corporate ethical governance and accountability: Malaysian evidence of self-regulating ethical culture / Norazamina Mohamed - Mohamed, Norazamina (2013)
Technology advances, competitive rivals and new innovation have changed the business world. What is not changed is the “profit-oriented” mind. Initially, it was a small scale of “profit-oriented” but then it evolves to immense scale of “profitoriented” as to achieve as much as possible high financial return. Evidences of businesses collapse indicate the business world is full with “greedy” and “corrupted” businessmen and practitioners. Therefore, it is recommended for the companies to embark on Corporate Ethical Governance and Accountability and to follow Applied Corporate Governance that view corporate governance not only on the aspect of structuring, operating and controlling but also with the purpose to achieve culture based on sound business ethics by concerning all stakeholders and by complying to all related regulations. The companies can carry out the utmost “best practices” of good corporate citizen through ethical culture. The main purposes of this study are to investigate the existence and practices of ethical culture dimensions and company’s spirituality in Malaysian Public Listed Companies and to examine their relationships with employees’ ethical behaviour. The ethical leadership, ethical guidelines in COCC/TACOS/EH and stakeholder balance are companies’ self-regulating dimensions of ethical culture. In addition, a new variable, company’s spirituality is incorporated to stimulate the company’s culture. Briefly these dimensions describe leaders with role model, good relationship and moral characteristics, documented ethical guidelines as a guidance of expected behaviour and stakeholders considerations in all aspects of business dealings. While company’s spirituality is the intrinsic and extrinsic values held by the company. In achieving the objectives, exploratory design method with instrument development model is applied to explore and to generalize these dimensions. Findings from secondary data, interviews and participant observation are used as the input for questionnaire instrumentation. Exploratory data analysis, factoring analysis (exploratory and confirmatory), correlation analysis and regression analysis (simple, multiple, hierarchical) provide answers for the research objectives, questions and hypotheses. Interestingly, findings in participant observation and questionnaire survey have some similarities. All three ethical culture dimensions existed and are correlated to each other. Either individually or in combination of two, they do correlate positively with employees’ ethical behaviour. All have strong relationship with employees’ ethical behaviour except for ethical guidelines in COCC/TACOS/EH with moderate relationship. Stakeholder balance is more significant as its combination with other ethical culture dimensions show high variance in predicting the employees’ ethical behaviour. Combination between ethical leadership and ethical guidelines in COCC/TACOS/EH is significant but the lowest in predicting the employees’ ethical behaviour. Only ethical leadership and stakeholder balance are significant to explain employees’ ethical behaviour when combined all three ethical culture dimensions. Though company’s spirituality does not moderate the relationship between ethical culture dimensions and employees’ ethical behaviour, it is a significant predictor of employees’ ethical behaviour at all level of combination (individual or combination of two or three ethical culture dimensions) with better predicting percentage. Thus, recognizing company’s spirituality as part of ethical culture will improve organizational culture and its ethical performance. To conclude, the measurable items of ethical culture dimensions and company’s spirituality are practical for Malaysian companies’ internal assessment and for national ethical identity. Therefore, commitment of companies towards ethical culture is necessary to enhance corporate ethical governance and accountability.